The influence of organisational culture and job satisfaction on emotional intelligence and organisational performance of Malaysian administrative and diplomatic officers / Suganthi Supramaniam - Suganthi , Supramaniam (2020)
As a natural instinct of survival in a competitive environment, organisations inherently aim to achieve high organisational performance. Due to constant global challenges and the volatile environment, organisations are accosted with various challenges. An analysis of Malaysia’s ranking in the IMD World Competitiveness report secured a 12th position in 2014, which dropped to the 24th position in 2017. As public servants play a pivotal part in meeting the competitiveness challenge of a country, this highlights a potential issue in the performance of the public service in improving the nation’s productivity. Hence, this thesis explores the effects of emotional intelligence on organisational performance in the civil service environment, with an emphasis on organisational culture and job satisfaction. In addition, the study aims to analyse the ingrained influence of emotional intelligence on the performance of Administrative and Diplomatic Officers in the civil service. This research further develops a holistic framework that links emotional intelligence, organisational performance, organisational culture and job satisfaction. This study intends to contribute to the developing literature and knowledge base on EI and OP through OC and JS, this may assist practitioners and researchers who are deliberating on the value of EI on OP and further research. This quantitative study collected data from the public administration officers based in Putrajaya and Kuala Lumpur. The data was obtained via a Likert type-scale questionnaire completed by 365 Administration and Diplomatic Officers and analysed using Smart PLS 3.2.6. This study contributes to a better understanding of organisational performance specifically in the public sector, due to the new knowledge created by this research. This research is based on the Social Intelligence Theory and the Theory of Hierarchy Needs. The Social Intelligence Theory emphasises on the ability of an individual to realise and recognise ones’ feelings and also the feelings of others. It allows one to be aware of self-management, self-awareness and knowing others in relationship management. As for the Theory of Hierarchy of Needs, it places importance on fulfilment of physiological, safety and self-actualisation that are needed for job satisfaction. The main finding of this research indicates that emotional intelligence has a positive direct effect on organisational performance. The constructs of emotional intelligence consisting of self-management, self-awareness, social awareness and relationship management play an important role in improving performance of public administrators. This highlights the need to establish emotional intelligence as one of the determinants of organisational performance and simultaneously find ways in ensuring it is prioritised in the public administration domain. The findings also reveal that emotional intelligence has a positive indirect effect on organisational performance through organisational culture. This indicates that emotional intelligence has the ability to influence organisational performance through organisational culture. The findings have implications for government human resources policies related to recruitment, training and development and organisational performance that are targeted at producing better outcomes and services to the general public.